Re-experiencing Street Signage with Augmented Reality around the City of Macau - Lio, Si Weng; Martins de Abreu, F. (11th International Conference on Digital and Interactive Arts (ARTECH2023), 2023)

Beyond Physical Boundaries—Organising a Virtual Exhibiton with NFTs for an International Conference - Estadieu, Gerald; Ng, S.O.K.M.; Martins de Abreu, F.; Farinha, D.F. (ARTECH 2023 - 11th International Conference on Digital and Interactive Arts, 2023)

Experience the Past in the Present with Immersive Technologies - Chang, Tin Lan; Martins de Abreu, F. (Multimodus’22 - 1st International Conference on Sound and Image in Art & Design, 2022)
Countless historical sites worldwide have become unrecognisable based on their historical context. Many are cultural heritage structures with significant historical and aesthetic importance. The majority have not been well preserved; worse, some were demolished (Stenning, 2015). Furthermore, structures are part of a dynamic and changing environment, and their location within the original landscape is not always clear. People have gradually forgotten cultural traditions as environments where historical stories took place, and the look and feel have been corrupted. Immersive Virtual Reality (V.R.) allows us to relive and explore the past. However, in the Pearl River Delta Region, specifically Macau S.A.R., V.R. is still in its infancy and is not frequently used for reproducing historical sceneries. Our research focuses on reproducing heritage structures and scenery based on scarce historical information. It shows how to incorporate facts and memories into the design and create engaging, immersive experiences in V.R. scenery that takes place, both inside and outside of a cultural heritage site that has lost its original appearance. Following this, a prototype was created with specific parameters relating to past and present sceneries. We partially reproduced an existing building complex currently being used for creative and commercial purposes, but it was a shelter for the poor and a house for old ladies to live in. There were not enough facts or images linked to the inner space in the past. Inadequate information allows audiovisual scene creators to be more imaginative. The prototype focuses on a functional design that integrates cultural traits tied to local industries. The researcher used image processing software, and web 3D tools (A-Frame 1.1.0). Users can navigate by virtually “walking” and starting the visual tour; simultaneously, the story unfolds as the timeline progresses. After entering, the users jump from the present to a specific era in the past. With audio guidance, users enter the private space, shared areas, working space, etc. Users can interact with objects from the virtual scenes while the interface displays relevant audiovisual introductions. Users could utilise the virtual system to learn how the old ladies led their daily lives in the Pearl River Delta Region and grasp the local single ladies’ group lifestyle at a specific time in the past (Kwong, 2020). The interactive experience enhances the users’ interest; additionally, the users become more familiar with the region’s traditional customs. With this approach, we can create old stories using modern technology. A-Frame provides users with great convenience and can be used by any Internet browser without relying on professional V.R. devices. The content from this usage provides a greater understanding of our heritage buildings and their historical context to the wider community. This could be used in other heritage sites worldwide to reproduce and maintain structural qualities over time. This immersive experience could be a means to navigate the past while in the present. This application could benefit exhibition developers, and visitors, notably in exhibition guided tours, virtual tours inside museums, or educational assisted historical storytelling.